2018
DOI: 10.1007/s11060-018-2876-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between programmed cell death ligand-1 expression and extracranial metastasis in intracranial solitary fibrous tumor/hemangiopericytoma

Abstract: PD-L1 is frequently expressed in intracranial SFT/HPCs, and diffuse or intense PD-L1 expression might be associated with the early occurrence of extracranial metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…[3,6] A thorough literature review focusing on metastatic SFT in the pre-WHO 2016 era and WHO I SFT/HPC in the post-WHO 2016 era revealed a total of 14 cases, referred in particular as malignant SFTs (Table 1). [5,6,8,10,15,2633] Data analysis showed no gender predominance (male: female, 3:4). The median age at initial tumor onset was 42 years, and there was a mean lag time of 8.74 years before metastasis took place.…”
Section: Discussionmentioning
confidence: 99%
“…[3,6] A thorough literature review focusing on metastatic SFT in the pre-WHO 2016 era and WHO I SFT/HPC in the post-WHO 2016 era revealed a total of 14 cases, referred in particular as malignant SFTs (Table 1). [5,6,8,10,15,2633] Data analysis showed no gender predominance (male: female, 3:4). The median age at initial tumor onset was 42 years, and there was a mean lag time of 8.74 years before metastasis took place.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the metastatic tumors shrank after 6 months. Programmed cell death ligand-1 (PD-L1) is frequently expressed in intracranial SFT/HPCs, and diffuse or intense PD-L1 expression might be associated with the early occurrence of extracranial metastasis ( 27 ). A combination of SRS and targeted drugs may improve the local control rate and extend survival time, but multicenter prospective large-sample clinical trials are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…have recently demonstrated that PD-L1 is commonly expressed in intracranial SFT/HPCs and that increased PD-L1 expression is associated with earlier extracranial metastases. [19] Further research into the use of PD-L1 inhibitors for the treatment of SFT/HPC is necessary.…”
Section: Discussionmentioning
confidence: 99%